Hacking Diversity: The Politics of Inclusion in Open Technology Cultures by Christina Dunbar-Hester (review). - Garda, Maria B. (Technology & Culture, 2024)
"Hacking Diversity: The Politics of Inclusion in Open Technology Cultures" by Christina Dunbar-Hester explores the lack of diversity within open technology communities and the efforts of activists and social change advocates to address this issue. The book takes an ethnographic approach, focusing on the everyday practices of the respondents. It critically examines power dynamics within these communities and highlights the need for social justice. The book also discusses the limitations of representation politics and calls for a deeper understanding of global equity. Overall, "Hacking Diversity" provides valuable insights into diversity issues in the North American tech industry and serves as a useful resource for historians of technology.